SAFE TRAFFIC, REFLECTED IN THE DAILY NEWSPAPER CRISANA (2021) - Ungur-Brehoi, Carmen (International Journal of Legal and Social Order, 2021)
Accidents and informative-preventive materials have always had a special echo in the media, whether we refer to the written press, radio, television or online journalism, arousing the interest of the public eager for fresh and exciting information. This article aims to observe the current importance of safe traffic in a local newspaper during 2021 (until the time of writing this material) and to identify the most interesting news and stories on this topic. The researched materials could be divided into several categories, due to their specificity: information, prevention, accidents and materials related to traffic safety.